UTILIZATION OF Abandoned LAND FOR PUBLIC INTEREST DEVELOPMENT IN INDONESIA IN THE PERSPECTIVE OF AL-QURA'N AND HADITH - Wibowo, Agung (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
. . The need for land is increasing over time to meet basic human needs and on the other hand there is no increase in land area in Indonesia. However, there are also many individuals and legal entities who control land that is not utilized in accordance with the nature of the land rights and the purpose of granting the rights, which results in abandoned land. Reviving abandoned land or dead land from the perspective of the Qur'an and Al-Hadith in the study of land theology is an effort to protect the environment so that it avoids damage. The context of the hadith of reviving dead land (Ihya al-mawat) in Indonesia in the current conditions of course must look at the existing conditions so that its application is more beneficial for the general public by utilizing abandoned land for development in the public interest. Legal protection for parties who control abandoned land in good faith is also provided with compensation if the land becomes the object of land acquisition for development in the public interest. Of course, to utilize abandoned land, you must follow the positive legal provisions governing land regulations in Indonesia.